A Rare Pediatric Giant Cell Tumor of the Clivus Bone, H3.3 p.Gly35Trp-mutated: Case Report and Mini-review of the Literature - Gabriele Gaggero; Teresa Battaglia; Virginia Andreotti; Andrea Rossi; Marta Ingaliso; Davide Taietti; Claudia Milanaccio; Gianluca Piatelli; Valerio Gaetano Vellone (Turkish Archives of Pediatrics)
Introduction: Giant cell tumor of bone (GCTB) is a rare, typically benign neoplasm that primarily affects long bones in adults, with clival involvement being extremely rare, particularly in pediatric cases: a mini-review shows a total of 28 described cases, of which only 5 were truly pediatric (within 14 years of age). Surgery is the treatment of choice, and Denosumab is reported to be the most effective drug therapy. To date, the GCTB’s molecular hallmark is the somatic mutation p.Gly34Trp, at the H3F3A gene (H3.3 p.Gly34Trp mutation), but in this case, the mutation H3.3 p.Gly35Trp was identified.